GE_GERICHTE P/11204/2011 vom 26. Januar 2012 - GE Cour de justice (2012)
MINORITÉ(ÂGE); MAJORITÉ(ÂGE); DÉTENTION PROVISOIRE; PROLONGATION ; COMPÉTENCE | PPMIN.27; CPP.225; CPP.226; CPP.222; CPP.224; CPP.221